Silicic acid biogeochemistry in the Gulf of California: Insights from sedimentary Si isotopes - Pichevin, L.E.; Ganeshram, R.S.S.; Reynolds, B.; Prahl, F.G.; Pedersen, T.F.F.; Thunell, R.C.; McClymont, E.L. (Paleoceanography, 2012)
Iron is considered to play a large role in the cycling of Si in Fe limited regions of the ocean but little is known about its role in Si biogeochemistry outside these areas. Here, we present published sediment trap data, new nutrient profiles and high resolution sedimentary records (Si isotopes, Biogenic silica%, N% and C%) from the Gulf of California, a non-Fe limited region, to investigate the history of Si cycling in this highly productive basin. Modern nutrient profiles show that silicic acid in subsurface waters is in excess relative to nitrate and therefore incompletely utilised during moderate winter upwelling events. Modern data however suggest that during intense upwelling episodes, silicic acid is preferentially utilised relative to nitrate by the biota, which we suggest reflects transient iron limitation. Our new δ30Si record from the Guaymas Basin shows dramatic variations at millennial time-scales. Low δ30Si values synchronous with Heinrich events are interpreted as resulting from the decline in Si(OH)4 utilisation at times of decreased upwelling strength, while nearly complete Si(OH)4 utilisation was observed at times of invigorated upwelling and increased opal burial during the Holocene, the Bølling-Allerød and the last glacial period. We attribute the complete utilisation of Si(OH)4 to the occurrence of transient Fe limitation at these times. Our study highlights the importance of Fe limitation on Si and C cycling in coastal upwelling regions and suggests that upwelling dynamics, in combination with Fe availability, have the potential to modulate marine Si distribution and opal burial even at short time-scales.
EPrint Processing Status: Full text deposited in DRO
Keywords: Biogeochemical cycles; Climate; Millennial timescale; Paleoceanography; Upwelling.